2020
DOI: 10.1371/journal.pone.0241061
|View full text |Cite
|
Sign up to set email alerts
|

Dramatic long-term restoration of an oak woodland due to multiple, sustained management treatments

Abstract: We measured 34 years of plant community change in a degraded oak woodland undergoing ecological management. Management included regular prescribed fire, control of white-tailed deer populations, repeated sowing of a diverse seed mix, and removal of invasive plants. We tracked change with several conservation metrics. Time series analysis showed no significant changes over time in either plant species richness or the Shannon-Weiner diversity index. Floristic Quality Assessment measures—the Floristic Quality Ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 58 publications
2
5
0
Order By: Relevance
“…Given the similarities in total native cover, but dramatic differences in dominance of functional groups between control (ruderal forbs) and sown (C 3 perennial grasses) locations, future studies should investigate whether reinvasion rates vary among these two plant communities. Our results are consistent with the prediction that degraded oak woodlands exhibit low recovery potential for matrix and conservative species without native seed addition (Glennemeier et al, 2020;Lamb et al, 2022;Packard, 1997). and Sanicula odorata (C = 2)) dominated forb cover in control transects.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Given the similarities in total native cover, but dramatic differences in dominance of functional groups between control (ruderal forbs) and sown (C 3 perennial grasses) locations, future studies should investigate whether reinvasion rates vary among these two plant communities. Our results are consistent with the prediction that degraded oak woodlands exhibit low recovery potential for matrix and conservative species without native seed addition (Glennemeier et al, 2020;Lamb et al, 2022;Packard, 1997). and Sanicula odorata (C = 2)) dominated forb cover in control transects.…”
Section: Discussionsupporting
confidence: 90%
“…Unlike most grassland species, many herbaceous species in woodlands (especially conservative forbs) produce low quantities of seed and are unavailable in commercial trade (Ladwig et al, 2020), which has likely limited the research and use of seed mixes in woodland restoration (Mottl et al, 2006). Consequently, it remains poorly known whether sowing species‐rich seed mixtures can promote the floristic recovery in degraded oak woodland (Brudvig et al, 2011; Glennemeier et al, 2020), and increase biotic resistance to non‐native invasion (Schuster et al, 2018). A few previous studies indicate that woodland seed additions may promote floristic recovery (Glennemeier et al, 2020) or reduce non‐native reinvasion (Wragg et al, 2021), although these studies did not examine establishment rates of sown species or compare changes in native plant community properties between sown and non‐sown locations at the same site.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the conifer-removal plots, the number of species appearing or disappearing was relatively high, and thus plant species composition may be changing over the short term. The rapid change in species composition after the treatment is typical in similar restoration projects (e.g., Glennemeier et al 2020 ), and this implies that long-term monitoring is necessary. We conclude that conifer removal on the biodiversity-rich seepage wetlands in the Circum-Ise Bay region can be a prioritized option for managers to conserve their unique plant composition, diversity, and cultural association with local people.…”
Section: Discussionmentioning
confidence: 99%
“…In a 20-year study of restored prairie in Kansas, differences in plant community diversity did not become apparent between restoration approaches altering soil heterogeneity until 16 years after planting (Baer et al, 2020). A longitudinal study of a single site in northeastern Illinois showed consistent plant diversity across 34 years, driven by decreases in non-native species and increases in native species (Glennemeier et al, 2020). Many restoration projects set up regular plant monitoring, but sampling is not always repeated consistently.…”
mentioning
confidence: 99%